Предпосылки развития управления маркетингом в виноградарско- винодельческих предприятиях - Фрейдис, Е.И. (Культура народов Причерноморья, 2013)
В статье рассмотрены предпосылки развития управления маркетингом в виноградарско-
винодельческих предприятиях. Выделен ряд современных экономических проблем, ограничивающих их
развитие. Автором отмечен широкий ассортимент выпускаемой виноградарско-винодельческими
предприятиями Автономной Республики Крым продукции: столовые сухие, креплёные, десертные и
полусладкие и шампанские вина. Разработаны предложения относительно повышения эффективности
управления маркетингом в них. У статті розглянуто передумови розвитку управління маркетингом в виноградарсько-
виноробних підприємствах. Виділено ряд сучасних економічних проблем, що обмежують їх розвиток.
Автором відзначений широкий асортимент продукції, що випускається виноградарсько-виноробними
підприємствами Автономної Республіки Крим: столові сухі, кріплені, десертні та напівсолодкі і
шампанські вина. Розроблено пропозиції щодо підвищення ефективності управління маркетингом в них. The most typical of the viticulture and wine industry enterprise were selected in the article. The
economic indicators of the viticulture and wine-making enterprises of the Autonomous Republic of Crimea are
examined. A number of the current economic issues limiting the development of wineries, highlighted in the
article. The preconditions for the development of marketing management in viticulture and wine-making
enterprises are discussed. Growth in revenue from the sale of wine and wine materials and the reduction of
revenue from the sale of grapes are marked by the author. The reduction in sales volumes of grapes are noted in
the article. This leads to the filling of the domestic market of foreign products. Reduction of land and an increase
in the degree of depreciation of fixed assets and increase gross profit margin was marked by the author. A wide
assortment of viticulture and wine production is noted in the article. Dry wines, semi-sweet wines, sweet wines
and sparkling wines are produced in the wineries of the Autonomous Republic of Crimea. Proposals to improve the effectiveness of marketing management in viticulture and wine-making enterprises, by creating a marketing
department, which will increase the volume of sales, market share, profits are developed.